A Studi Bobot Badan Ternak Terhadap Produksi Susu Kambing Sapera (Capra aegagrus hircus) di Peternakan El Farm Yogyakarta: Studi Bobot Badan Ternak Terhadap Produksi Susu Kambing Sapera (Capra aegagrus hircus) di Peternakan El Farm Yogyakarta - Hermawati, Nurul Fauziah; Nuraeni, Nunur (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2024)
Background: Milk production of dairy goats (Capra aegagrus hircus) is influenced by several factors including age of livestock, environment, feeding, breed, and body weight. Goats with heavy body weight generally have high milk productivity. Sapera goats are a type of dairy goat with high milk production, reaching 1.5-2 liters per head per day. Purpose: The purpose of this study was to determine the effect of body weight on milk production of Sapera goats at El Farm Yogyakarta. The material of this research is Sapera dairy goats that are in lactation 1 and 2 as many as 19 heads. Methods: The research method was carried out by taking data on milk production and body weight. Milk production data were taken every morning and evening. Body weight data is obtained by measuring the chest circumference of Sapera goats every week. Results: The results of the analysis showed that the body weight of Sapera goats had no significant effect on milk production with a correlation value of 0.014. Signification between variables x and y =0.95 > alpha 0.05.  Conclusion: There is no influence between body weight on milk production in Sapera goats.